1984
DOI: 10.1001/archotol.1984.00800330003001
|View full text |Cite
|
Sign up to set email alerts
|

Human Endolymphatic Duct: An Ultrastructural Study

Abstract: \s=b\The fine structure of the human endolymphatic duct was observed by transmission electron microscopy. Wel l \x=req-\ preserved specimens were obtained after fixation of inner ear tissue by perilymphatic perfusion. The morphologic findings seemed to be in accordance with earlier propositions that the human endolymphatic duct may be involved in endolymph resorption. The duct was found to contain otoconialike bodies, suggesting that the endolymphatic duct and sac in man may also play a role in the turnover of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
4

Year Published

1986
1986
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 14 publications
(1 reference statement)
4
41
0
4
Order By: Relevance
“…The exact border between endolymphatic duct and sac is not clearly defined and is the subject of discussion. Recently, the endolymphatic duct has been suggested to be a short single lumen tubule only 2 mm long (24,30). The endolymphatic sac is variable in size and irregular in outline.…”
Section: Discussionmentioning
confidence: 99%
“…The exact border between endolymphatic duct and sac is not clearly defined and is the subject of discussion. Recently, the endolymphatic duct has been suggested to be a short single lumen tubule only 2 mm long (24,30). The endolymphatic sac is variable in size and irregular in outline.…”
Section: Discussionmentioning
confidence: 99%
“…The ED forms a narrow tubule with a single layer epithelium leading to the endolymphatic sac (ES) through the vestibular aqueduct (VA) of the petrous bone. The ED is surrounded by a loose interstitial connective tissue (CT) also filling up numerous bone cavities parallel to the aqueduct (Friberg et al 1984). The interstitial cells are organized in a tissue network structure with prominent intercellular and cell-extracellular matrix (ECM) contacts (Hultgard-Ekwall et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Waste products from the rest of the inner ear are believed to be transported to the ES by the longitudinal flow of endolymph [1]. Studies on the human ES with transmission electron microscopy (TEM) have revealed degenerated cell products [11], red blood corpuscles, discarded otoconia and collagen fibres [12] in the lumen. TEM studies on ES from patients with Ménière's disease (MD) and acoustic neuroma showed that luminal contents often included degenerated cell products originating mainly from the ES itself [13,14].…”
Section: Introductionmentioning
confidence: 99%